Behavioral changes in group-housed dairy calves infected with Mannheimia haemolytica - Hixson, C.L.; Krawczel, P.D.; Caldwell, J.M.; Miller-Cushon, E.K. (Journal of dairy science, 2018)
Monitoring sickness behavior may improve identification, management, and welfare of sick animals. The objective of this study was to characterize components of sickness behavior in group-housed dairy calves, using an experimental disease challenge model with Mannheimia haemolytica (MH). Holstein bull calves (aged 3–7 weeks; 58.0 ± 12.0 kg of body weight) were group-housed based on age and body weight in sand-bedded pens (6 calves/pen, 6.6 m2/calf) and provided pasteurized waste milk (8 L/d) 2×/d and grain concentrate ad libitum. Within group, calves were randomly assigned to 1 of 2 treatments: (1) inoculation at the tracheal bifurcation with 3 × 109 cfu of MH suspended in 5 mL of sterile phosphate buffered saline (PBS) followed by a 120 mL wash PBS (MH; n = 12, 3/pen), or (2) inoculation with 5 mL + 120 mL of sterile PBS only (control; n = 12, 3/pen). Rectal temperature and health scores were collected from d 0 to +6 of the challenge. A range of behaviors, including feeding patterns and social interactions, were recorded from video from d 0 to +2. The challenge model resulted in calves experiencing a mild disease state: rectal temperatures of MH calves were elevated throughout the challenge compared with control calves, peaking at 12 h postinoculation (39.2 vs. 38.9°C; standard error = 0.14). Many behavioral responses were subject to treatment by day effects, with calves generally becoming less active following inoculation with MH and then returning to baseline. Affected behaviors surrounding feeding included milk feeding time, frequency of competitive displacements, and concentrate feeding time. Lying time was similarly subject to treatment by day effects, and MH calves also spent more time lying on their left side compared with their right (604 vs. 471 min/h; standard error = 32), whereas control calves expressed no laterality. Duration of social lying did not differ, but frequency of social lying bouts decreased in MH calves following inoculation (0.44 vs. 0.75 bouts/h; standard error = 0.04). Social grooming was initiated less by MH calves (0.78 vs. 1.96 min/h; standard error = 0.38), but they tended to receive more social grooming for a greater duration of time (1.59 vs. 1.25 min/h; standard error = 0.13). Overall, we found that infected calves exhibited reduced grooming, feeding, and social interactions, suggesting that these behavioral changes may be useful indicators of early stages of respiratory disease.